CONCEPTUALISING ISLAMIC CREDIT CARDS BASED ON MUSHĀRAKA MUTANĀQISA - Ahmed M. Alkhan; M. Kabir Hassan; Rashedul Hasan (Bank Indonesia, 2020)
The purpose of this paper is to conceptualise an Islamic credit card (or mushāraka card) based on the Islamic principles of mushāraka mutanāqisa. A qualitative methodology was employed, with qualitative content analysis used on AAOIFI Shari’a Standard (SS) No. 12 “Sharikah (Musharaka) and Modern Corporations” to derive key rulings and controls for mushāraka mutanāqisa, which were then used to conceptualise an Islamic credit card based on mushāraka mutanāqisa. Theoretically, it should be possible to develop an Islamic credit card based on the Islamic rulings of mushāraka mutanāqisa. The concept provided in this paper could be adopted as a pilot project by Islamic retail banks. Evidence suggests that a new revised standard for credit cards (included within AAOIFI Shari’a Standard (SS) No. 2) was under construction while this research was being undertaken. Therefore, it was not possible to review what perhaps may be relevant information for conceptualising a new Islamic credit card. The research intends to fill the gap by qualitatively conceptualising an Islamic credit card based on a mushāraka mutanāqisa in an in-depth manner, especially with the use of AAOIFI as a base for the conceptual analysis.